The effect of curing methods and loading time on shear bond strength of orthodontic brackets / Faisal Ismail El-Sayed Bahnasi - El-Sayed Bahnasi, Faisal Ismail (2010)
The introduction of light cured materials in dentistry had led to the development of different curing devices with different curing times. Objectives: to evaluate the effect of light curing units. curing times and the effect of delay loading on shear bond strength (SBS) of orthodontic brackets. Methods: 120-extracted human teeth were divided into 12-groups of 10-teeth each and bonded with stainless-steel brackets by using 3M linitek Transhond XT composite. Specimens NNerc cured with halogen. LED and plasma arc lights with different times. 6-groups of the specimens were tested after 5rnin in shear with Shimadzu Precision Universal Tester at a cross-head speed of Irnm/min until brackets dehonded. The rest of specimen were stored in distilled water at 37°C for 2411 and then subjected to the same loading. The bond strength was calculated by dividing the force in Newton to the surface area. Data were subjected to statistical analysis to identify differences in mean SE3S with respect to curing time and time of force loading. Results: There was no significant dif1rcnce between 6-groups with dehonded fbrce after 5mm. However the other 6- groups with debonded force after 24h showed a statistically significant difference, group 10. LED 20s was significantl y higher than LED lOs. plasma arc 6s and plasma arc lOs. Conclusion: SBS of all curing light devices with applied force after 5 min gave values more than the normal range: therefore arch wire can be inserted at the same visit. Within limit of this study. halogen (20 and 40s). LED (10 and 20s) and plasma arc (6 and lOs) can be used to bond brackets, however if high is needed. LED 20s with loading time after 2411 is recommended.